2008
DOI: 10.4049/jimmunol.181.1.408
|View full text |Cite
|
Sign up to set email alerts
|

Functional Tolerance of CD8+ T Cells Induced by Muscle-Specific Antigen Expression

Abstract: Skeletal muscles account for more than 30% of the human body, yet mechanisms of immunological tolerance to this tissue remain mainly unexplored. To investigate the mechanisms of tolerance to muscle-specific proteins, we generated transgenic mice expressing the neo-autoantigen OVA exclusively in skeletal muscle (SM-OVA mice). SM-OVA mice were bred with OT-I or OT-II mice that possess a transgenic TCR specific for OVA peptides presented by MHC class I or class II, respectively. Tolerance to OVA did not involve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…CFSE-labeled OVA-specific Th cells (OT-II cells) neither proliferated nor expressed the activation marker CD69 after transfer into NOH mice ( Figure 1E). This was consistent with previous studies showing failure of OT-II cells to proliferate in response to OVA expressed as transgenic self antigen and has been explained by their limited affinity in particular for autoantigen (35,40,46). In summary, glomerular autoantigen was constitutively presented by DCs in the renal LNs, but only OT-I cells proliferated in response.…”
Section: Figuresupporting
confidence: 81%
See 3 more Smart Citations
“…CFSE-labeled OVA-specific Th cells (OT-II cells) neither proliferated nor expressed the activation marker CD69 after transfer into NOH mice ( Figure 1E). This was consistent with previous studies showing failure of OT-II cells to proliferate in response to OVA expressed as transgenic self antigen and has been explained by their limited affinity in particular for autoantigen (35,40,46). In summary, glomerular autoantigen was constitutively presented by DCs in the renal LNs, but only OT-I cells proliferated in response.…”
Section: Figuresupporting
confidence: 81%
“…Mechanistic analysis revealed that Th cells acted by stimulating cross-presenting DCs in secondary lymphatics to permit cytotoxic effector function, whereas CTLs activated by unlicensed DCs ("help-less" CTLs) were programmed to die after secondary antigen encounters (43,44). Analogous mechanisms were reported in models used to examine different antigens or expression sites (45)(46)(47). Furthermore, Th cells may regulate the CTL effector phase in nonlymphatic organs (34,35,46).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Using transgenic SM-OVA mice (selectively expressing OVA in skeletal muscle), bred with OVAspecific TCR Tg mice (OT-I or OT-II, restricted by MHC class I or class II, respectively) Olivier Boyer and his group elegantly showed that tolerance to muscle Ag (OVA neoAg) may not involve clonal deletion, anergy or an increased regulatory T-cell compartment as in other organs. Instead, they identified a tolerance mechanism in which CD4+ T-cells are tolerant by ignorance, whereas CD8+ T-cells become refractory to induction of a cytotoxic response [48]. Nevertheless, FOXP3 + regulatory T-cells (Treg), which main subset is also CD4+ CD25+, were recently to play a role in IIMs.…”
Section: T-cell: Myofiber Interactions In Polymyositismentioning
confidence: 98%